2013
DOI: 10.1002/cite.201200213
|View full text |Cite
|
Sign up to set email alerts
|

Application of Adsorptive Reactors for the Reverse Water Gas Shift Reaction

Abstract: Application of Adsorptive Reactors for the Reverse Water Gas Shift ReactionCarbon dioxide can serve as a C 1 building block for chemical syntheses. To increase the reactivity of CO 2 it may be reduced to carbon monoxide with hydrogen using an adsorptive reactor for the reverse water gas shift (rWGS) reaction. Both model simulations and experimental studies have been conducted to demonstrate the proof of principle and to assess the performance of an adsorptive rWGS reactor. The results show that application of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 6 publications
0
6
0
1
Order By: Relevance
“…Low operating pressures were selected for the RWGS process in the present study because the methanol-synthesis reactions (reactions and ) are promoted at high pressures (e.g., P = 50–70 bar for a conventional methanol-synthesis process). The effect of the methanol-synthesis reactions at low pressures was calculated at T = 250 °C, P = 1–10 bar (similar to the pressure in the literature , ), and H 2 /CO 2 = 3 (feed gas). The results (data not shown) of the equilibrium composition show little change with increasing pressure, and a small amount of methanol was formed (e.g., 0.41 mol % MeOH with P = 10 bar and 0.11 mol % MeOH with P = 5 bar).…”
Section: Resultsmentioning
confidence: 89%
See 2 more Smart Citations
“…Low operating pressures were selected for the RWGS process in the present study because the methanol-synthesis reactions (reactions and ) are promoted at high pressures (e.g., P = 50–70 bar for a conventional methanol-synthesis process). The effect of the methanol-synthesis reactions at low pressures was calculated at T = 250 °C, P = 1–10 bar (similar to the pressure in the literature , ), and H 2 /CO 2 = 3 (feed gas). The results (data not shown) of the equilibrium composition show little change with increasing pressure, and a small amount of methanol was formed (e.g., 0.41 mol % MeOH with P = 10 bar and 0.11 mol % MeOH with P = 5 bar).…”
Section: Resultsmentioning
confidence: 89%
“…The high requirement of the R value can be fulfilled by SERP according to the experimental studies in the literature; for the application of MRs, experimental investigations are still required. In the following sections, only the high values of R = 0.80–0.99 were considered.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Adsorptive reactors have been proposed for a variety of industrially important reactions, which have been concisely reviewed elsewhere 1. In our own research group, the Claus process, hydrogen cyanide synthesis, and the retro‐shift conversion for CO 2 functionalization have been the subject of detailed theoretical and experimental investigations to improve the conversion by in situ adsorption of the common by‐product, water vapor, on 3A zeolite 12–16. Of these systems, only the Claus process for H 2 S‐SO 2 synproportionation was considered worthy of further examination since the adsorptive HCN synthesis exhibited excessive uncontrollable side‐reactions, whilst the kinetics of the retro‐shift reaction proved too slow at the lower operating temperatures between 200 and 300 °C 12.…”
Section: Concrete Test Casesmentioning
confidence: 99%
“…Preliminary studies on the endothermic rWGS reaction as well as in other exothermic processes like the Deacon or Claus processes have demonstrated that this concept is an attractive alternative. In this work, modeling and simulation of the cyclic steady‐state (CSS) and further technical optimization have been carried out.…”
Section: Introductionmentioning
confidence: 99%